2020
DOI: 10.1097/01.asw.0000655380.86380.7b
|View full text |Cite
|
Sign up to set email alerts
|

Using Subepidermal Moisture Level as an Indicator of Early Pressure Damage to Local Skin and Tissue

Abstract: OBJECTIVE Inflammation triggered by tissue injury increases blood flow to the injured area, resulting in fluid accumulation below the epidermis known as subepidermal moisture (SEM). This accumulation can be assessed using an SEM scanner. The primary aim of this study was to determine whether levels of SEM from repeated measures at a localized area confirm the absence of a pressure injury at that site in healthy participants. METHODS Fifty patients atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…The progression of cell death and tissue necrosis causes gradual local alterations of the mechanical properties of the injured tissues that can, in turn, change the distributions of strains and stresses in forms that are likely to exacerbate the evolving injury, for example, through development of inflammatory oedema and localised rigour mortis in skeletal muscles 65,69,75,120‐122 . Localised inflammatory oedema, one of the earliest signs of cell death in PUs/PIs, may be detectable via measurement of a biophysical marker called the biocapacitance of tissues 15,121‐132 . Reperfusion that follows a period of prolonged ischaemia may further increase the extent of tissue damage as it involves release of damaging oxygen free radicals 95‐100,133 …”
Section: Tissue Damage Due To Mechanical Loading Repair and Individua...mentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of cell death and tissue necrosis causes gradual local alterations of the mechanical properties of the injured tissues that can, in turn, change the distributions of strains and stresses in forms that are likely to exacerbate the evolving injury, for example, through development of inflammatory oedema and localised rigour mortis in skeletal muscles 65,69,75,120‐122 . Localised inflammatory oedema, one of the earliest signs of cell death in PUs/PIs, may be detectable via measurement of a biophysical marker called the biocapacitance of tissues 15,121‐132 . Reperfusion that follows a period of prolonged ischaemia may further increase the extent of tissue damage as it involves release of damaging oxygen free radicals 95‐100,133 …”
Section: Tissue Damage Due To Mechanical Loading Repair and Individua...mentioning
confidence: 99%
“…65,69,75,[120][121][122] Localised inflammatory oedema, one of the earliest signs of cell death in PUs/PIs, may be detectable via measurement of a biophysical marker called the biocapacitance of tissues. 15,[121][122][123][124][125][126][127][128][129][130][131][132] Reperfusion that follows a period of prolonged ischaemia may further increase the extent of tissue damage as it involves release of damaging oxygen free radicals. [95][96][97][98][99][100]133 The microclimate between the skin and the support surface or any skin-contacting medical device or object plays an important role in the development of PUs/PIs.…”
Section: Tissue Damage Due To Mechanical Loading Repair and Individua...mentioning
confidence: 99%
“…In a systematic review of the Cochrane database, Moore and Patton (2019) indicated a low certainty of the evidence (downgraded twice for study limitations and imprecision) in using Braden and Waterlow risk assessment to reduce PI/PU incidence when compared to clinical judgement (Moore & Patton, 2019). Moreover, diagnosis of PI/PUs is recorded only after visual confirmation, when damage at the macroscopic tissue level has already occurred (Gershon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The paradigm of PI/PU prevention, management and treatment has been largely weighted towards treating category I PI/PUs once visible skin redness manifests at the surface level. Advances in research and improved understanding of PI/PU pathophysiology establish that early pressure‐induced tissue damage occurs microscopically at the cellular level (Bader & Oomens, 2018; Gefen, 2018; Gershon, 2020; Gefen & Ousey, 2020; Ross & Gefen, 2019; Van Damme et al, 2020). Objective, evidence‐based diagnostic devices, that detect the earliest signs of PI/PU damage, and thereby enabling earlier, targeted interventions are critical in achieving sustained prevention of PI/PUs.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with other studies and suggest that when there is a change in SEM measurements this corresponds with changes in PU development. Thus, SEM measurement may be a useful method for detecting early non‐visible PU development (Bates‐Jensen, McCreath, Kono, Apeles, & Alessi, 2007; Bates‐Jensen, McCreath, Nakagami, & Patlan, 2018; Bates‐Jensen, McCreath, & Patlan, 2017; Bates‐Jensen, McCreath, & Pongquan, 2009; Bates‐Jensen et al, 2008; Bates‐Jensen, Reilly, Hilliard, Patton, & Moore, 2020; Gefen & Gershon, 2018; Gershon, 2020; Guihan et al, 2012; Harrow & Mayrovitz, 2014; Kim, Park, Ko, & Jo, 2018; Moda Vitoriano Budri et al, 2020; O'Brien, Moore, Patton, & O'Connor, 2018; Okonkwo et al, 2020; Park, Kim, & Ko, 2018; Raizman, MacNeil, & Rappl, 2018; Smith, 2019). SEM is described as this accumulation of fluid below the epidermis and changes in SEM due to interstitial fluid accumulation and localized edema are accepted as biomarkers in the development of PUs (Okonkwo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%